The novel circular RNA HIPK3 accelerates the proliferation and invasion of hepatocellular carcinoma cells by sponging the micro RNA-124 or micro RNA-506/pyruvate dehydrogenase kinase 2 axis. Issue 3 (1st March 2022) - Yu, Qiangfeng; Chen, Wenxiang; Li, Yiming; He, Jun; Wang, Yu; Yang, Sijia; Zhou, Jianyin
ABSTRACT: Circular RNAs (circRNAs) have been confirmed to be associated with the progression of various cancers, including hepatocellular carcinoma (HCC). However, the role and mechanism of circHIPK3 in HCC are still unclear. To investigate its function, circHIPK3 expression was first determined by RT–qPCR in HCC tissues or cells. Functionally, cell proliferation and invasion were investigated by CCK-8, EdU, or Transwell assays. In terms of understanding the mechanism, the interaction of the circRNA HIPK3/micro RNA 124 (miRNA 124) or micro RNA 506 (miRNA506) /PDK2 regulatory loop was verified by dual-luciferase reporter gene assay. In addition, a xenograft tumor model was established to confirm the impact of circHIPK3 on the growth of HCC cells in vivo . We found that circHIPK3 was upregulated in HCC patients and associated with clinical characteristics, while miR-124 and miR-506 were downregulated in HCC patients. Additionally, we proved that knock down of circHIPK3 remarkably suppressed the proliferation and invasion of HCC cells. Mechanistically, circHIPK3 directly bound to miR-124 or miR-506 and inhibited their expression, and PDK2 was a target gene of miR-124 or miR-506. Moreover, circHIPK3 overexpression reversed the inhibitory effect of miR-124 or miR-506 on HCC progression. miR-124 or miR-506 could also suppress tumorigenesis of HCC cells by PDK2. Furthermore, in vivo evidence confirmed that knock down of circHIPK3 inhibited tumor formation. We suggest that circHIPK3 can accelerate the proliferation and invasion of HCC cells by sponging miR-124 or miR-506 to upregulate PDK2, which is the underlying mechanism of circHIPK3-induced HCC progression.